2019
DOI: 10.1504/ijsom.2019.097036
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid cellular manufacturing system design with cellularisation ratio: an integrated mixed integer nonlinear programming and discrete event simulation approach

Abstract: This study investigates hybrid cellular manufacturing system design where products with highly similar process routes are formed as manufacturing cells, and products with dissimilar routes are produced in a process layout. A cell similarity threshold, cellularisation ratio (C-ratio), is proposed for product assignment to cells and process layout, and integrated into a mathematical modelling-based cell formation approach. The cell formation phase is carried out with the proposed mathematical model. Several case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Egilmez et al [6] explored the high similarity of manufacturing processes leading to work cell formation. At the end of their research, they concluded that there is a link between good work cell formation and a high similarity index of the cell equipment.…”
Section: Standardization and Modular Structurementioning
confidence: 99%
“…Egilmez et al [6] explored the high similarity of manufacturing processes leading to work cell formation. At the end of their research, they concluded that there is a link between good work cell formation and a high similarity index of the cell equipment.…”
Section: Standardization and Modular Structurementioning
confidence: 99%
“…Bilgen and Doğan (2015) analyzed the value-added distribution integrated with production planning to reduce the cost of distribution of dairy products [8]. Eğilmez et al (2019) applied discrete event simulation to hybris cellular manufacturing with integrated mixed integer nonlinear programming [9], and Grillo et al (2017) considered a multi-purpose mathematical model in which different demand situations [10]. Paul et al (2017) proposed a three-tier supply chain network [11].…”
Section: Literature Surveymentioning
confidence: 99%